(3CHQGgGe dfchdf h GdKhQI GdCeQjcjI GdKGfjI (B/s - (3eGcajQShf, LjeS es; (3aGjRI(B;(3CMeOs ((3eUQ (B:s (3GdOGQ GdOhdjI ddESJKeGQGJ GdKbGajI T(B.(3e(B.(3e ,s, 2001)
(3jbOe JQLeI gPG GdcJGH ddbGQF GdYQHj djjJYQa Ydi Gge LhGfH TNUjI CHQGge dfchdf HYO Gf JeJ JQLeJg dYOI dZGJs
Keywords: (3TNUjGJs; (3CHQGge dfchdfs